THE ROLE OF SAMBALPURI HANDLOOM IN THE ECONOMIC GROWTH OF BARGARH DISTRICT ODISHA - Kunal Mishra, Dr. Tushar Kanti Das (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
When Human Beings civilized, handloom has been an integral part of men. In this sense handloom has been an oldest industry of the world. From ancient period to the modern period handloom industry is closely connected with the economic growth of the land. So to say the Handloom Industry has a major role in the economic growth of India also. India has a rich, diverse and unique handloom tradition since long. History speaks that, weaving has been an extremely developed craft since Indus Valley Civilisation. From Historical records it is evident that, India is a country where dyeing, printing and embroidering has been a continuing process. The array of handloom textiles varies in different regions of India because of its Geography, Climate, Local Culture, Social Customs and availability of raw materials. A number of raw materials like cotton, silk, jute and bamboo etc. are used for creating fabrics in India. But silk and cotton predominates the Indian weaving tradition. The craftsman does most of the work by hand but due to eruption of modern technology the process has become simpler and faster. The fabrics of India are unique for the workmanship, colours and durability. Every State in India is known for a particular handloom which reflect in the vivid life style, culture and geography. Moreover Odisha is not an exception to it. Odisha is a land of rich culture, rich monuments, rich temples and rich natural beauties. All these reflect in the handloom production of different regions of Odisha. So far the present topic is concerned, it relates to the Western region of Odisha. In the western region of Odisha, Bargarh is a prominent place for its culture, tradition and craftsmanship